Aging related cognitive changes associated with Alzheimer's disease in Down syndrome. Issue 6 (20th May 2018) - Firth, Nicholas C.; Startin, Carla M.; Hithersay, Rosalyn; Hamburg, Sarah; Wijeratne, Peter A.; Mok, Kin Y.; Hardy, John; Alexander, Daniel C.; ,; Strydom, André
Abstract: Objective: Individuals with Down syndrome (DS) have an extremely high genetic risk for Alzheimer's disease (AD), however, the course of cognitive decline associated with progression to dementia is ill‐defined. Data‐driven methods can estimate long‐term trends from cross‐sectional data while adjusting for variability in baseline ability, which complicates dementia assessment in those with DS. Methods: We applied an event‐based model to cognitive test data and informant‐rated questionnaire data from 283 adults with DS (the largest study of cognitive functioning in DS to date) to estimate the sequence of cognitive decline and individuals' disease stage. Results: Decline in tests of memory, sustained attention/motor coordination, and verbal fluency occurred early, demonstrating that AD in DS follows a similar pattern of change to other forms of AD. Later decline was found for informant measures. Using the resulting staging model, we showed that adults with a clinical diagnosis of dementia and those with APOE 3:4 or 4:4 genotype were significantly more likely to be staged later, suggesting that the model is valid. Interpretation: Our results identify tests of memory and sustained attention may be particularly useful measures to track decline in the preclinical/prodromal stages of AD in DS whereas informant‐measures may be useful in later stages (i.e. during conversion into dementia, or postdiagnosis). These results have implications for the selection of outcome measures of treatment trials to delay or prevent cognitive decline due to AD in DS. As clinical diagnoses are generally made late into AD progression, early assessment is essential.